(Invited) Novel Fuel Production Based on Sonochemistry and Sonoelectrochemistry. (3rd July 2019) - Islam, Md Hujjatul; Lamb, Jacob J.; Lien, Kristian M.; Burheim, Odne Stokke; Hihn, Jean-Yves; Pollet, Bruno G.
Abstract : Sonochemistry has been used in many applications where it is employed to improve both catalytic and synthetic processes; whereas, sonoelectrochemistry has been used in various studies including organic syntheses, environmental (soil and water) treatments, water disinfection and various analytical procedures. In the ongoing energy transition from a fossil-based energy economy, society requires energy forms that can be readily stored and transported. This can be achieved using rechargeable batteries, biofuels and hydrogen. Hydrogen (H2 ) is an attractive fuel source due to its rather high specific energy compared to other conventional fuels. Power ultrasound could be an attractive alternative since the ultrasonication of water produces H2 . Alternatively, biogas production could be another fuel source. However, lignocellulose presents a bottleneck due to its' rigid and obstinate structure. Power ultrasound could be adopted as a pretreatment of lignocellulosic materials to improve their utilisation in the production of biogas.